The Effect of pH on the Preparation of Electrically Conductive and Physically Stable PANI/Sago Blend Film via in situ Polymerization - Ali Mohsin, M. E.; Shrivastava, Nilesh K.; Arsad, Agus; Basar, Norazah; Hassan, Azman (Frontiers in Materials, 2020)
This study attempts to prepare electrically conductive and physically stable PANI/Sago starch films by a simple one-pot synthesis method using ultrasound irradiation technique. To attain physical stability of the prepared films, the pH of the PANI/Sago dispersion was varied (2, 4, 6, 7, 9 and 11 pH) before drying. The effect of pH on the structural properties (1H NMR and FT-IR), electrical conductivity (E.C), optical properties (UV-VIS) and morphology (FE-SEM) of the blends was studied. 1H NMR results revealed that at low pH (2 and 4), degradation of sago starch took place and as the pH increases, deprotonation of PANI takes place. The findings of 1H NMR were ably supported by E.C results, which showed gradual decrease in conductivity until pH 7 and then a drastic drop was noticed for pH 9 and 11. UV-Vis findings reveals that, as the pH increases, PANI deprotonates from emeraldine salt form to emeraldine base form. The morphological results were complimentary with 1H NMR and FT-IR, while revealing different morphologies: coral like morphology with voids in them for blends with pH 2 and 4; well-connected and smooth morphology for blends with pH 6 and 7; and well-connected but with loose flake like morphology for blends with pH 9 and 11. Overall, the PANI/Sago blend with pH 6 was found to be electrically conductive and physically stable.